ARTICLE 27 OF COMPETITION LAW AND WHAT LIES BENEATH - Saputro, Perdana A. (Indonesia Law Review, 2011)
This article discuss about Article 27 of Law No. 5 Year 1999 on the Restriction of Monopoly Practices and Unfair Business Practices (“Competition Law”). One may wonder the rigorousness to the application of Article 27 which arguably could ban any merger which meets market test without conducting any competitive assessment. For this, the law has been presumed that the acquisition or controlling of large market share from merger is per se illegality. Further, the effects of Article 27 would be discussed in this paper. A merger review itself is not an easy task and tends to bring complex issues that one needs to be dealt with. Things get more complicated when one deals with the merger application in developing countries since there are various aspects that need to be taken account by the respective antitrust authority (including Indonesia) Obviously, every country needs to set up its competition law in accordance with its own economic characteristics and conditions. Many have argued as to point out the severe condition in market as a result of high concentration of competition. But more of them argued otherwise, as it could positively pushed on the market. This article would also include best practices from US and EU competition law practices regarding the issue at hand, as well as the relationship of merger control and practices in developing countries. The article offers suggestion with regard to the current approach to Article 27 of the Competition Law and from EU and US best practice which could be used for the benefit of Indonesia’s competition law especially to the application of Article 27.